On p-superlinear equations with a nonhomogeneous differential operator - Aizicovici, Sergiu
We consider a nonlinear elliptic equation driven by a nonhomogeneous differential operator and with a (p−1)-superlinear Carath´eodory reaction. Our formulation incorporates as a special case equations monitored by the p-Laplacian. Using variational methods coupled with truncation techniques and comparison principles,